In silico identification and validation of microRNAs from the genome of Solanum lycopersicum targeting Groundnut bud necrosis orthotospovirus - Nivedha, M.; Harish, S.; Angappan, K.; Karthikeyan, G.; Kumar, K.K.; Murugan, M.; Jayakanthan, M. (Physiological and molecular plant pathology, 2023)
Tomato, an extensively cultivated edible crop is prone to many viral pathogens. Among them, bud necrosis incited by Groundnut bud necrosis orthotospovirus (GBNV) causes huge yield loss (80–100%). Out of all known strategies for viral disease management in plants, RNA interference (RNAi) mediated approaches have greater potential in managing viral diseases. Small RNAs especially microRNA (miRNA) play a major role in RNAi-mediated defense in plants. Using in silico analysis, we have identified the possible tomato encoded miRNA that have the potential to interact with GBNV-mRNA. The results revealed that, sly-MIR9479-3p, sly-MIR10529, sly-MIR397-5p, sly-MIR10528, sly-MIR477-3p, and sly-MIR6024 predicted by the computational algorithms viz., miRanda, psRNA target, RNA22 and RNA hybrid have the potential to interact with different GBNV-ORFs. Conserved complementary sequences of sly-MIR10529 and sly-MIR6024, targeting GBNV genome regions (ORF2 and ORF5), were confirmed in multiple GBNV isolates. The expression of Sly-miR-10529 (1.72-fold increase),Sly-miR-6024 (2.83-fold decrease) and their corresponding glycoprotein and coat protein gene expression were quantified through q-RT-PCR. These predicted miRNAs can offer useful information for the production of antiviral agents/RNAi mediated transgenic crop plants against GBNV in tomato. [Display omitted] •Identified a set of microRNAs binding with the GBNV viral Open Reading Frames (ORFs).•Seven sly-microRNAs have a high level of sequence complementarity with the GBNV virome.•Sequences of sly-MIR10529 and sly-MIR6024 were conserved in different isolates of GBNV.•Stem-loop qRT-PCR indicates a differential expression of sly-MIR10529 and sly-MIR6024 during GBNV infection in tomato.